Interval bidding in a distribution elicitation format. Issue 51 (2nd November 2017) - Mahieu, Pierre-Alexandre; Wolff, François-Charles; Shogren, Jason; Gastineau, Pascal
ABSTRACT: Interval bidding allows people to report a range of values for a non-market good. Herein, we allow people to choose their distribution over this range endogenously. We consider a multiplicative error model explaining the willingness to pay (WTP) which is estimated using a feasible generalized least squares estimator. We apply our framework to a representative sample of the French population who were asked about the valuation of a bear conservation programme. We find that most participants prefer stating their WTP as a range rather than a point, but the shape of the distribution greatly varies across people. Our results support the use of the interval bidding with endogenous distribution approach in valuation studies.